Periprosthetic distal femur fractures around total knee replacements: A comprehensive review - Al-Jabri, Talal; Ridha, Mohamed; McCulloch, Robert Allan; Jayadev, Chethan; Kayani, Babar; Giannoudis, Peter V. (Injury, 2023)
With a growing number of patients undergoing total knee replacements globally, coupled with an elderly population, the incidence of periprosthetic fractures around total knee replacements is increasing. As such, this is a highly topical subject that is gaining increasing interest within the orthopaedic community. This review provides a narrative synthesis of the most contemporary literature regarding distal femoral periprosthetic fractures. We review the related epidemiology, initial patient evaluation, the evolution and relevance of the classification systems and treatment options, particularly related to endoprosthetics and hybrid fixation constructs. The latest orthopaedic evidence related to this topic has been included.